Integrasi Pancasila dengan Teknologi Artificial Intelligence dalam Pengembangan Kurikulum Pendidikan Nasional : Integration of Pancasila with Artificial Intelligence Technology in the Development of the National Education Curriculum - Rahma Aulia Zulfa; Aida Nur Amalina; Shofa Aulia Azzahra; Devina Dwi Prahastiwi; Pundy Widya Sari; Indy Raya Febiana (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The rapid advancement of Artificial Intelligence (AI) has brought significant transformations across various sectors, including education. On the one hand, AI offers vast potential to enhance learning effectiveness, personalize curricula, and promote equitable access to education. On the other hand, its implementation also raises ethical, cultural, and ideological challenges that must be addressed in the Indonesian context. Therefore, Pancasila, as the state foundation and national philosophy, should serve as the normative framework for the development of AI-based curricula. This study aims to analyze a model of integrating Pancasila with AI in the design of the national education curriculum that is adaptive to global developments while preserving national identity. The research employs a descriptive qualitative approach through literature review, educational policy analysis, and philosophical examination of Pancasila’s values. The findings indicate that such integration can be realized through three main strategies: (1) formulating adaptive AI-based curricula aligned with the moral and ethical principles of Pancasila, (2) utilizing AI as a pedagogical tool to strengthen inclusivity and equal access to education, and (3) reaffirming Pancasila as an ethical filter in the development and implementation of educational technology. In conclusion, integrating Pancasila with AI in national curriculum development not only supports the quality of education relevant to the digital era but also safeguards national identity amid globalization.